Convergence of Human Development Index: case study of foreign direct investment in ASEAN - Kaukab, M. Elfan; Surwandono, Surwandono (Business: Theory and Practice, 2021)
This article examines the role of bilateral FDI and income convergence in affecting HDI increase in countries with middle HDI in ASEAN. The ASEAN Economic Community has been developing and it is expected that the gaps between nations can be covered. This article explores how economic intervention through HDI and income convergence can boost HDI improvement. The writers examine the presence of a statistically significant causal relationship between source country’s GDP, home country’s GDP, source country’s FDI towards the home country, source country total FDI, home country total FDI, and the percentage of source country FDI towards source country total FDI with both countries HDI convergence. Measurement is carried out using the generalized method of moments. Based on yearly samples of high HDI countries (Malaysia, Thailand, Singapore) couple with medium HDI countries (Laos, Vietnam, Cambodia, Myanmar, Indonesia, and Philippine) during 2013–2017 period, the writers find statistically significant impact of home country GDP, source country FDI towards all countries, and FDI percentage of the home country compared to all countries.